Smallville: Season 10, The Final Season - Welling, Tom, 1977-; Mack, Allison, 1982-; Durance, Erica; Freeman, Cassidy, 1982-; Hartley, Justin, 1977-; Blue, Callum, 1977- (Burbank, CA : Warner Bros. Entertainment : Distributed by Warner Home Video, 2011)
In this 22-Episode Season 10, super heroes emerge from the shadows, only to be driven underground by a public that labels them vigilantes. At the same time, otherworld forces of darkness gather, presenting Clark Kent with the greatest challenge of his young life. The world he calls home and the people he loves, including Lois Lane, who now shares his secret and his life, need a champion. They shall have one.
Disc 1. Lazarus ; Shield ; Supergirl ; Homecoming -- disc 2. Isis ; Harvest ; Ambush ; Abandoned -- disc 3 Patriot ; Luthor ; Icarus -- disc 4 Collateral ; Beacon ; Masquerade ; Fortune -- disc 5. Scion ; Kent ; Booster ; Dominion -- disc 6 Prophecy ; Finale.
Special features: commentaries ; unaired scenes ; Smallville: coming home: cast and creators reflect on the landmark 200th episode ; experiences ; tranformative events on the way to his final destiny ; My fathers, my son ; How do we do music video.
New DVD 2023 Fall.
English dialogue; English, French or Spanish subtitles. English subtitles for the deaf and hard of hearing.
Subtitled in English ; Subtitled in French ; Subtitled in Spanish ; Translated from English.
Keywords: Superman -- (Fictitious character); Television serials; Science fiction television programs